Synthesis of Quinolines via a Metal‐Catalyzed Dehydrogenative N‐Heterocyclization. Issue 2 (15th August 2016) - Chelucci, Giorgio; Porcheddu, Andrea
Abstract: Efficient ruthenium‐, rhodium‐, palladium‐, copper‐ and iridium‐catalysed methodologies have been recently developed for the synthesis of quinolines by the reaction of 2‐aminobenzyl alcohols with carbonyl compounds (aldehydes and ketones) or the related alcohols. The reaction is assumed to proceed via a sequence involving initial metal‐catalysed oxidation of 2‐aminobenzyl alcohols to the related 2‐aminobenzaldehydes, followed by cross aldol reaction with a carbonyl compound under basic conditions to afford α, β‐unsaturated carbonyl compounds. These aldehydes or ketones can be also generated in situ via dehydrogenation of the related primary and secondary alcohols. In the final step cyclodehydration of the α, β‐unsaturated carbonyl compound intermediates gives quinolines. Good yields of quinolines were also obtained by reacting 2‐nitrobenzyl alcohols and secondary alcohols in the presence of a ruthenium catalyst. Finally, aniline derivatives afforded also a useful access to quinolines by the reaction with 1, 3‐propanediol or 3‐amino‐1‐propanol, or in a three‐component reaction with benzyl alcohol and aliphatic alcohols. Abstract : Efficient ruthenium‐, rhodium‐, palladium‐, copper‐ and iridium–catalysed methodologies have been recently developed for the synthesis of quinolines by the reaction of 2‐aminobenzyl alcohols with carbonyl compounds (aldehydes and ketones) or the related alcohols. The reaction is assumed to proceed via a sequence involving initial metal‐catalysed oxidation of 2‐aminobenzyl alcohols to the related 2‐aminobenzaldehydes, followed by cross aldol reaction with a carbonyl compound under basic conditions to afford α, β‐unsaturated carbonyl compounds. Good yields of quinolines were also obtained by reacting 2‐nitrobenzyl alcohols and secondary alcohols in the presence of a ruthenium catalyst.